An Analysis of Students' Anxiety in Speaking English at UPT SMPN Satap 2 Batu in Leppangeng - Desy Syahrani; Ibrahim Manda; Sitti Aisa; Sam Hermansyah (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study employed a descriptive qualitative approach to examine whether students experience anxiety in learning English, particularly in speaking. The data were collected through questionnaires and interviews, involving 14 eighth grade students at UPT SMPN SATAP 2 Batu. The objectives of this research were to identify the forms of speaking anxiety experienced by eighth grade students at UPT SMPN SATAP 2 Batu and to analyze the internal and external factors that influence the students’ speaking anxiety. The results show that the most dominant forms of anxiety are nervousness when speaking in front of the class (71%), fear of making mistakes (64%), and anxiety when speaking without preparation (64%). Other factors include feeling inferior to more proficient peers (50%) and fear of being laughed at (57%). The causes of anxiety were categorized into internal factors, such as low self-confidence, past experiences, and limited vocabulary, as well as external factors, including social pressure, peer attitudes, and teachers’ feedback approaches.